Removal of Zn (II) and Cu (II) Ions from Industrial Wastewaters Using Magnetic Biochar Derived from Water Hyacinth - Benias C. Nyamunda; Terrence Chivhanga; Upenyu Guyo; Fidelis Chigondo (Journal of Engineering)
This study evaluates the effectiveness of magnetic biochar (Fe2O3-EC) derived from water hyacinth in the removal of Cu+2 and Zn+2 from aqueous solution. Fe2O3-EC was prepared by chemical coprecipitation of a mixture of FeCl2 and FeCl3 on water hyacinth biomass followed by pyrolysis. The adsorbent was characterized by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) coupled with energy dispersive spectroscopy (EDX). Batch adsorption studies on the effects of temperature, biosorbent dosage, contact time, and initial metal ion concentration were carried out. Fe2O3-EC exhibited optimum contact time, biosorbent dosage, and pH values of 65 min, 1.2 g, and 6, respectively. Fe2O3-EC exhibited strong magnetic separation ability and high sorption capability. Metal ion adsorption onto the biochar conformed to the Langmuir isotherm. Kinetic studies revealed that the adsorption process followed pseudo-second-order model. The calculated thermodynamic parameters showed that the adsorption process was feasible and exothermic in nature. These results have demonstrated that the use of Fe2O3-EC in metal ion removal could provide an alternative way to manage and utilize this highly problematic invasive species.